Exploring the Awareness and Adoption of Online Healthcare Consultations in Metro Vigan, Philippines - Marianne Joyce C. Pilorin, Carl Andrei L. Osalvo, Dainelyn G. Pacapac, Jan Dexter A. Rafal, Hazel May S. Sabio, Marlbour Jon B. Valera, Greggie A. Talingdan (South Eastern European Journal of Public Health, 2024)
Introduction: The COVID-19 pandemic accelerated the adoption of telehealth, offering a safer alternative to traditional in-person care. However, its adoption remains limited, especially among socioeconomically disadvantaged groups. This study investigates the awareness and usage of online healthcare consultations in Northern Philippines, focusing on socio-demographic factors. Objectives: This research explored the respondents' adoption of online consultation in Metro Vigan. Specifically, it looked into the participants' socio-demographic profile, sources of health information, and awareness of online healthcare consultations, as well as the relationships between these variables to inform targeted health interventions. Methods: A descriptive-correlational design was used, with a survey administered to 100 respondents to assess demographics, awareness, and adoption of online healthcare consultation.Results: Most respondents were young, primarily female, Roman Catholic, single, and unemployed, with moderate monthly incomes. Social media was the dominant information source (98%), while print media was less preferred (28%). A high percentage (81%) was aware of online healthcare consultations, largely due to COVID-19. There were positive correlations between consultation awareness and family income, occupation, and religion, while age, gender, education, and information sources showed no significant correlation. Conclusions: The findings indicate that adoption and utilization of online healthcare consultations are influenced by socio-economic factors, with monthly family income, occupation, and religion playing a significant role. Social media was essential for disseminating health information, emphasizing its impact on public health participation.